Technical appendix: The DeepTree layout and rendering engine - Florian Block; Michael S. Horn; Brenda Caldwell Phillips; Judy Diamond; E. Margaret Evans; Chia Shen (Harvard University, 2012)
This technical report provides details regarding the DeepTree layout and rendering engine